CRIMINAL SANCTIONS IN THE FIELD OF TAXATION BETWEEN LEGAL PROVISIONS IN INDONESIA AND LAW IN CHINA - Ria Berlian Tambunan (Airlangga Development Journal, 2023)
Taxes are a source of state revenue, it can be seen that income from the tax sector is one of the largest sources of state revenue. One of the efforts to increase state revenue is to enforce the law in the field of taxation. In order to support law enforcement, the imposition of sanctions is carried out correctly, precisely and does not overlap so that it can provide legal certainty and benefits both from the government side and from the taxpayer side. the author compares tax law with China regarding criminal acts of taxation, imposition of sanctions such as law enforcement for taxpayers who commit violations and/or crimes that violate the provisions stipulated by law. The results of the comparison regarding the provisions of tax law in China, it is necessary to reform the tax law, that is, the imposition of sanctions is enough to only use fine administrative sanctions if the state's losses have been returned by the perpetrators of crime, implement a blacklist system against tax evaders and tax violations, imposition of sanctions against Tax officials should be included as a codified unit in the tax law.